Pengaruh Pajak Tangguhan dan Struktur Modal Terhadap Kinerja Keuangan Perusahaan Pada Perusahaan Dagang - Surya Sanjaya; Muhammad Irsan; Fahri Effendi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study was conducted with the aim of testing and analyzing deferred tax and capital structure on the financial performance of trading companies listed on the Indonesia Stock Exchange. The population in this study were all trading companies listed on the Indonesia Stock Exchange, while the samples that met the criteria for sampling were observed for five years and as many as six trading companies were listed on the Indonesia Stock Exchange. This research approach uses associative research. Data collection techniques in this study using documentation techniques. and the analysis technique used is multiple linear regression analysis, hypothesis testing and coefficient of determination. The results showed that partially deferred tax had no effect on financial performance, capital structure had no effect on financial performance, while simultaneously deferred tax and capital structure had no effect on financial performance.